Farming Efficiency and Productivity in Increasing Farmers' Income - Aerin Regina Putri; Satya Apriliansyah (Professorline, 2026)
Farming is an important sector in supporting food security and rural economies. The efficiency of the use of production inputs and the level of agricultural productivity play an important role in determining farmers' income. This paper discusses the relationship between efficiency, productivity, and farmers' income with a descriptive-analytical approach. The results of the study show that increasing efficiency in land use, labor, and fertilizer has a positive impact on productivity and income. Productivity-enhancing strategies, such as the adoption of agricultural technology, crop rotation, and farming diversification, have also been proven to improve farmers' welfare. This approach can be the basis for agricultural development policies that are oriented towards increasing income and sustainability of farming.